Apakah Pengungkapan Sustainability Report Berpengaruh Pada Kinerja Keuangan? Kasus Dari Bursa Efek Indonesia - Violeta, Elice; Azmi, Zul; Suci, Rama Gita (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to analyze the effect of sustainability report disclosure on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange. The sustainability report is measured based on three main aspects—economic, environmental, and social—referring to the Global Reporting Initiative (GRI) standards. Financial performance is measured using Return on Assets (ROA), with secondary data obtained from annual reports and sustainability reports of companies over a specified period. This research adopts a quantitative approach using multiple linear regression analysis. The results indicate that, partially, only the environmental aspect has a significant effect on ROA, while the economic and social aspects do not show a significant effect. However, simultaneously, the three aspects of the sustainability report have a significant influence on financial performance. These findings suggest that companies demonstrating a strong commitment to environmental management tend to achieve better financial performance. This study provides important implications for companies in enhancing transparency and environmental responsibility.